Analisis Karakteristik Mutu, Aspek Teknologis, dan Potensi Pengembangan Gula Merah Berbasis Nira Kelapa Sawit dan Nira Kelapa - Hendro Kartiko; Helmi Haris; Aji Jumiono; Syahrir Akil; Sri Widowati (Jurnal Ilmiah Pangan Halal, 2026)
This study aimed to analyze the quality characteristics, technological aspects, and development potential of brown sugar derived from oil palm sap and coconut sap from a food technology perspective. The research employed a systematic review approach combined with descriptive-comparative analysis of primary research data and relevant scientific literature. The primary data consisted of three treatments: P1 (100% oil palm sap), P2 (50% oil palm sap + 50% coconut sap), and P3 (100% coconut sap). The results indicated that variations in sap composition were associated with differences in the chemical characteristics of the resulting brown sugar. The highest glucose content was observed in treatment P2 at 4.45%, followed by P3 at 2.47%, while the lowest value was found in P1 at 1.40%. In terms of total energy, treatment P3 showed the highest value at 408.27 kcal/100 g, followed by P2 at 398.37 kcal/100 g, and P1 at 390.59 kcal/100 g. Organoleptic evaluation revealed that all treatments exhibited similar basic characteristics, namely sweet taste, brown color, and normal odor. The findings suggest that the quality of brown sugar is influenced by the source of raw materials, sap handling, heating process, and post-production stages, including cooling, packaging, and storage. Overall, oil palm sap demonstrates potential as an alternative raw material for brown sugar production, either as a single source or in combination with coconut sap, particularly through improvements in processing technology, quality standardization, and product diversification.